Northrop Frye and the Tragedy of Identity in Moby-Dick - Lammers, David (My University, 1995)
The following discussion of Northrop Frye and Herman Melville is based on the theoretical framework outlined in Words With Power which emphasizes the "demonic" and "titanic" elements in the ascent and descent of the hero's quest. The study focusses upon Frye's archetype of the labyrinth and the Biblical typology which aids the critic in the task of literary interpretation. Frye claims that "anyone interested in both the Bible and literature will eventually find himself revolving around the Book of Job like a satellite" (Frye WP 310). Melville's MobyDick is "interested" in the Bible more than any other source; it revolves around the mysteries therein which condemn the "titanic" elements that appear to lead to the discovery of a "Knowledge" or "Wisdom" related to Original sin. Thus, Ahab is a Promethean figure whose challenge of the demonic categorization of this area of imagery in the Bible is inextricably related to Job's challenge of God and subsequent invocation of Leviathan. In an application of Frye's theory of the patterns of ascent and descent imagery outlined in Anatomy of Criticism, The Secular Scripture, and Words With Power, chapters 1 & 2 examine the purely "demonic" descent of the quest hero and its "positive analogies" in the myth of Narcissus. Chapter 3 discusses the "titanic" descent quest in relation to its "presiding deity" Prometheus (Ahab), and chapter 4 briefly addresses the images of ascent surrounding Ishmael at the end of the novel. Notably, each chapter also examines the relation of the quest to patterns of Leviathan symbolism which are also represented in the image of the whale. Finally, the Conclusion reconsiders the Biblical Leviathan and Job's vision of "primal creation" which Frye points to in his verbal universe or axis mundi imagery.
Keywords: theoretical framework, demonic, titanic, Biblical typology, elements, original sin